Thực trạng sử dụng trí tuệ nhân tạo (AI) của giáo viên phổ thông Việt Nam - Lê, Anh Vinh; Đỗ, Đức Lân; Nguyễn, Minh Hải; Lê, Quang Quân; Vũ, Văn Luân; Bùi, Thu Hương; Lê, Anh Lan; Vũ, Kim Chi; Lương, Đình Hải (Tạp chí Giáo dục, 2025)
Artificial intelligence (AI) is becoming an important tool to support education with growing popularity at all education levels. Understanding teachers’ current use of artificial intelligence is essential for effectively exploiting this technology in schools. This survey of 34,571 secondary school teachers aims to describe how and to what extent AI is applied in educational contexts. The findings indicate that most teachers have used AI, with similar usage rates across demographic groups. Its main applications include designing teaching activities, creating lesson plans, and designing assessment materials. Notably, most teachers learn about AI through self-study. These results confirm that AI has become a popular support tool for teachers and highlight the urgent need for educational institutions to develop incentive mechanisms, evaluate effectiveness, and share implementation experiences, thus promoting teaching innovation amid digital transformation.